RC4 GGHN Cryptography Algorithm for Message Security - An-nissa, Shahira (Universitas Islam Sumatera Utara, 2022)
Cryptography is a technique that is generally used in security in the process of exchanging information in the form of text messages, picture messages, or others involving two or more users. There are many types and classifications of cryptography developed to date that are able to provide security for the information sent. Modern cryptography that is popular and widely used is the Rivest Cipher (RC4) algorithm. RC4 cryptography is a type of stream cipher, which processes units or input data at one time. This research will use a combination of several message character lengths, namely 50, 100, 250, 500, 1000, 2500, 5000, 10000 characters, and tested using several key lengths, namely 5, 10, 25, 50, 100 characters. from testing with message length parameters and keys then the results will be compiled into a table and described into an image for easy understanding. Research results show it can be concluded that the length of the key used in encryption does not significantly affect the effectiveness of the system processing time. In addition, the length of the text has a big influence in determining the length of the system process in encrypting and decrypting messages. the more the number of characters that will be sent, the higher the processing time required to perform the security process once using the RC4 GGHN cryptography algorithm